Adolescents and Retaliation Coping with Cyberbullying: Do Individual and Social Factors Matter? - Onditi, Hezron Zacharia (Papers in Education and Development, 2024)
Cyberbullying has been linked with a host of negative outcomes for adolescents. This study explored the role of child-parent -teacher-peer relationships (external social factors) and self-esteem and assertiveness (individual factors) in predicting the use of a retaliation coping strategy among adolescents. The study employed a cross-sectional research design, and a total of 778 secondary school adolescents aged 14 to 18 completed a self-report questionnaire. Results showed that adolescents with higher levels of self-esteem reported less likelihood of using the retaliation coping strategy in dealing with cyberbullying, while adolescents with greater levels of assertiveness reported a high likelihood of using retaliation. It was also found that older male adolescents are less likely to report the use of retaliation compared to female adolescents. Also, older adolescents who reported more positive parent-child relationships are more likely to use retaliation. Results further showed that highly assertive adolescents with more positive teacher relationships are less likely to use retaliation. Findings suggest gendered and age-specific education and intervention programmes that promote positive adolescents relationships with parents and teachers and responsible online assertiveness skills to cope with cyberbullying. Keywords: Cyberbullying, retaliation, coping, assertiveness, self-esteem